2020
DOI: 10.1101/2020.04.22.20075234
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Measuring Italian Citizens’ Engagement in the First Wave of the COVID-19 Pandemic Containment Measures: A Cross-sectional Study

Abstract: Background: In January 2020, the coronavirus disease 2019 (COVID-19) started to spread in Italy. The Italian government adopted urgent measures to hold its spread. Enforcing compliance to such measures is crucial in order to enhance their effectiveness. Engaging citizens′ in the COVID-19 preventive process is today urgent in Italy and around the world. However, to the best of our knowledge, no previous studies have investigated the role of health engagement in predicting citizens compliance to health emergency… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 60 publications
1
22
0
Order By: Relevance
“…According to this principle, a crucial step for the development of our campaign was the survey of a representative sample of the Italian population during the first phase of the emergency, which aimed at exploring people's literacy, attitudes, and levels of engagement toward COVID-19 prevention. The survey, which is discussed in more detail in another paper (Graffigna et al, 2020), confirmed the opportunity to change of people's attitudes toward prevention, rather than only to increase their literacy. Furthermore, it demonstrated the role of engagement in improving people's attitudes toward preventive measures during the COVID-19 emergency.…”
Section: Emotionalmentioning
confidence: 72%
See 2 more Smart Citations
“…According to this principle, a crucial step for the development of our campaign was the survey of a representative sample of the Italian population during the first phase of the emergency, which aimed at exploring people's literacy, attitudes, and levels of engagement toward COVID-19 prevention. The survey, which is discussed in more detail in another paper (Graffigna et al, 2020), confirmed the opportunity to change of people's attitudes toward prevention, rather than only to increase their literacy. Furthermore, it demonstrated the role of engagement in improving people's attitudes toward preventive measures during the COVID-19 emergency.…”
Section: Emotionalmentioning
confidence: 72%
“…After recruitment and informed consent, responders were asked to complete an online survey involving questions about health engagement, affective response, and behavioral responses to the COVID-19 pandemic. The full methodological details and results of this survey are reported in an extensive paper currently being submitted (Graffigna et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 In contrast, one-time cross-sectional investigation is tailored for the regions and countries with initial or subsequent peaks of transmission of epidemic waves (ie, Italy, Spain, and Wuhan). [3][4][5] The second issue is population selection. For regions with a low incidence of SARS-CoV-2, targeting specific population groups should be taken into account.…”
mentioning
confidence: 99%
“…In the United States of America, symptom-based (at least 10 days have passed since symptoms first appeared) and test-based strategies (negative results for SARS-CoV-2 detections from at least 2 consecutive respiratory specimens collected ≥24 hours apart) are proposed by the Centers for Disease Control and Prevention as the Return-to-Work criteria. 4 In Canada, health authorities justified allowing COVID-19 positive HCWs to return to work 10 days from the start of them having symptoms. 5 In Germany, home quarantine periods are recommended 14 days after being tested negative or without respiratory symptoms; in the case of staff shortages, the criteria of minimum 48 hours without symptoms and with 2 consecutive negative testing are applied.…”
mentioning
confidence: 99%